Hitherto Unrecorded Hydrophytes of Nal Sarovar Bird Sanctuary (A Ramsar Site) - Gamit, Vinesh; Tatu, Ketan; Gujar, Rakesh; Kamboj, R. D. (Indian Forester, 2021)
Nal Sarovar Sanctuary and the Ramsar Site in Gujarat is known for its diversity and abundance of migratory and resident-migratory waterbirds. Though it is also rich in hydrophytic and halophytic vegetation, relatively limited research work has been done on them till date. Seasonal monitoring of this wetland was carried out from 2016 to 2019 with habitat based stratified random sampling approach. During the study, a total of 19 hydrophyte species were recorded in 2019 of which 4 hydrophytes were never reported earlier from this wetland-based sanctuary. The four hydrophytes were Ceratophyllum demersum (a free-floating submerged hydrophyte), Utricularia stellaris (rooted submerged hydrophyte), Ottelia alismoides (a rooted submerged hydrophyte) and Limnophyton obtusifolum (an emergent hydrophyte). They were recorded in shallow water marshy habitats of the Nal Sarovar Sanctuary and Ramsar Site. They were found in association with other hydrophytes like Chara sp., Ipomoea aquatica and Nymphaea nouchali. Per cent cover value (determined using Daubenmire frame) for Ceratophyllum demersum and Utricularia stellaris was 1% each. On the other hand, Ottellia alismoides and Limnophyton obtusifolum were found to have 4% and 2% canopy coverage respectively at the site where they were recorded. They were recorded at a depth of about 80-100 cm and having turbidity in the range of 0.1 to 0.6 NTU and salinity ranging from 0.8 to 2 ppt.